Potential thermochemical conversion of bioenergy from Acacia species in Brunei Darussalam: A review - Ahmed A.; Abu Bakar M.S.; Azad A.K.; Sukri R.S.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Biomass; Carbon dioxide; Economics; Energy resources; Feedstocks; Forestry; Fossil fuel deposits; Fossil fuels; Gasification; Global warming; Investments; Pyrolysis; Acacia auriculiformis; Acacia mangium; Bio energy; Employment opportunities; Fossil fuel resources; Sustainable resources; Thermo chemical process; Thermochemical Conversion; Renewable energy resources